Acolhimento com avaliação e classificação de risco e qualidade dos serviços de urgência e emergência - Cabral, Karynne Borges (2015)
INTRODUCTION: The host strategy with risk assessment and classification (AACR) aims to reduce the risk of deaths considered preventable, the extinction of the screening conducted by the doorman or professional not trained and prioritization of care according to clinical criteria and not in order of arrival. Given the concern about the quality of emergency care services offered in public institutions and that nurses play a key role in the effectiveness of the AACR, this study aimed to identify how nurses perceive the AACR classifiers in the context of improving the quality of health services. GOAL: To analyze the perceptions of nurses about the quality of care in urgent and emergency services that has AACR. METHODOLOGY: A descriptive exploratory study with a qualitative approach. The data were collected through semi-structured individual interviews, recorded on digital media, performed with seven nurses working in AACR urgent and emergency units of Goiânia-GO, in May and June, 2014. RESULTS: While acknowledging the difficulties, all participants agreed that the AACR has contributed to improving the quality of emergency care and emergency units, especially because it prevents deaths in queues, prioritizing the care of critically ill patients to the detriment of less severe. The high demand and structural problems such as inadequate human resources, lack of basic materials for patient assessment and inadequate physical space, in addition to the inadequate functioning of public health care facilities were identified as hindering factors of the service. Among the aspects that facilitate the work and contribute to improving the quality of care in the industry, they indicate full staff, acquisition / availability of minimally materials needed for proper evaluation of the patient, presence of a guard / security and the knowledge of the population about this service strategy. Other suggestions included the adequacy of the physical structure and space guarantee that allows privacy for the risk assessment. CONCLUSIONS: The results of the study confirm that the urgent and emergency services share the same difficulties already described for all public primary health care of the population. Although the AACR will contribute to improving the quality of these services, much remains to be done to ensure minimum conditions for the good performance of professionals working in the sector and thus enhance the benefits it can bring to the care of their users.